Penerapan Prinsip Good Governace dalam Pelayanan Administrasi Bidang Bina Marga - Srihandayani Suprapto; Verawaty Harmain (Publikasi Indonesia, 2022)
This study aims to determine the application of the principles of good governance in the administrative services of the Highways Sector at the Department of Public Works and Spatial Planning, Gorontalo Province. The type of research used is descriptive qualitative. The results of the study indicate that the application of the principles of good governance in the administration service of the Highways Sector at the Department of Public Works and Spatial Planning of Gorontalo Province has not been implemented properly. This study uses the Indrajit approach (2002:5) about the main principles that form the basis of the implementation of Good Governance, namely; transparency, accountability, efficiency and participation. Of the four indicators used as benchmarks, there are 3 (three) indicators that have not been met, namely transparency, accountability, and efficiency. Meanwhile, 1 (one) other indicator, namely the participatory indicator, has been fulfilled. This can be seen from the involvement of outside parties such as contractors in every activity, especially in every decision making.